The effect of employee engagement on employee outcomes working from home moderated digital learning orientation - Indra Setiawan; Sinta Sundari Heriyanti (Institute of Computer Science (IOCS), 2023)
During the Covid-19 pandemic, the government told people to stay away from each other. Because of this, the company has a rule that says you can't work from home. Implementing the work-from-home (WFH) policy significantly affects how employees do their jobs. WFH makes employees less interested in their careers, which is terrible. This could be because employees find it hard to communicate and work with digital devices, so they need to learn how to use them. The goals of this study were to (1) determine how employee engagement affects employee outcomes when they WFH and (2) determine how digital learning orientation affects employee engagement and employee outcomes when they WFH. All of the people in this study are employees who work in the Greater Jakarta area of Indonesia and have a WFH policy or are in the process of making one. Samples were taken using a